Analisis Pengelolaan Arus Kas Dalam Menjaga Likuiditas di PT. Marisa Jaya Abadi - Audina Amanda Putri; Andrian Noviardy (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
In terms of maintaining the liquidity of PT Marisa Jaya Abadi, this study analyzes cash flow management. The method used was descriptive analysis, and data was collected through interviews and document studies. The research shows that the business has used several approaches to manage their cash flow, such as managing debt payments and accelerating the collection of receivables. However, to achieve ideal liquidity, these strategies still need to be improved. According to this study, PT Marisa Jaya Abadi should conduct regular cash flow evaluations to improve efficiency and financial stability.